Psoriatic Arthritis and Diabetes: A Population-Based Cross-Sectional Study - Jacob Dreiher; Tamar Freud; Arnon D. Cohen (Dermatology Research and Practice)
Background. Diabetes has been associated with psoriasis, but little is known about the association between psoriatic arthritis and diabetes. Methods. Patients diagnosed with psoriatic arthritis by a rheumatologist were compared to age- and sex-matched patients without psoriatic arthritis regarding the prevalence of diabetes in a population-based cross-sectional study using logistic multivariate models. The study was performed utilizing the medical database of Clalit, the largest healthcare provider organization in Israel. Results. The study included 549 patients with psoriatic arthritis ≥21 years and 1,098 patients without psoriatic arthritis. The prevalence of diabetes in patients with psoriatic arthritis was increased as compared to the prevalence in patients without psoriatic arthritis (15.3% versus 10.7%, value = 0.008). The difference was prominent among females (18.7% versus 10.3%, ) but not among males (11.2% in patients with and without psoriatic arthritis, ). In a multivariate analysis, psoriatic arthritis was associated with diabetes among females (OR = 1.60, 95% CI: 1.02–2.52, ) but not among males (OR = 0.71, 95% CI: 0.42–1.22, ). Conclusion. Our study suggests a possible association between psoriatic arthritis and diabetes in women. Women with psoriatic arthritis might be candidates for diabetes screening.